Development of the early fetal human thalamus: from a protomap to emergent thalamic nuclei - Maznah Alhesain; Ayman Alzu’bi; Ayman Alzu’bi; Ayman Alzu’bi; Niveditha Sankar; Niveditha Sankar; Charles Smith; Charles Smith; Janet Kerwin; Ross Laws; Susan Lindsay; Gavin J. Clowry (Frontiers in Neuroanatomy)
IntroductionMost of what is known about thalamic development comes from rodent studies, however, the increased proportion of human association cortex has co-evolved with increased thalamocortical connectivity. Higher order thalamic nuclei, relaying information between cortical regions and important in higher cognitive function, are greatly expanded.MethodsThis study mapped the emergence of thalamic nuclei in human fetal development (8–16 post conceptional weeks; PCW) by revealing gene expression patterns using in situ hybridization and immunohistochemistry for previously established thalamic development markers.ResultsIn the proliferative thalamic ventricular zone, OLIG3 and NR2F1 immunoreactivity marked the extent of the thalamus, whereas PAX6 and NR2F2 were expressed in gradients, suggesting an early protomap. This was also the case for post-mitotic transcription factors ZIC4, GBX2, FOXP2 and OTX2 which marked thalamic boundaries but also exhibited opposing gradients with ZIC4 expression higher anterior/lateral, and GBX2, FOXP2 and OTX2 higher in posterior/medial. Expression patterns became increasingly compartmentalized as development progressed and by 14 PCW recognizable thalamic nuclei were observed with, for instance, the centromedian nucleus being characterized by high FOXP2 and absent GBX2 expression. SP8-like immunoreactivity was expressed in distinct thalamic locations other than the reticular formation which has not been previously reported. Markers for GABAergic neurons and their precursors revealed the location of the prethalamus and its development into the reticular formation and zona incerta. No GAD67+ neurons were observed in the thalamus at 10 PCW, but by 14 PCW the medial posterior quadrant of the thalamus at various levels was infiltrated by GAD67+/ SOX14+ cells of presumed pretectal/midbrain origin. We compared expression of the neurodevelopmental disease susceptibility gene CNTNAP2 to these patterns. It was highly expressed by glutamatergic neurons in many thalamic regions by 14 PCW, sometimes but not always in conjunction with its upstream expression regulator FOXP2.ConclusionIn human discrete thalamic nuclei exhibiting discrete gene expression patterns emerge relatively early from a protomap of gene expression. The migration of GABAergic neurons into the thalamus occurs over a protracted period, first from the midbrain. Disruption of CNTNAP2 activity and function could be hypothezised to have a variety of effects upon thalamic development.